Multi-objective evolutionary optimization of UVB phototherapy of psoriasis through a 3-dimensional agent-based model - Cayetano, Arjay Caburnay (College of Engineering, University of the Philippines Diliman, 2011)
The interaction of various skin cells in determining our complexion is already intricate yet is even more complex in the presence of internal factors such as inflammation and external factors such as exposure to UV radiation (UVR). In this research, an agent-based model (ABM) was constructed in order to effectively capture the interactions between the skin and immune cells in the presence of psoriasis, an inflammatory skin disease, as well as their heterogeneous behavior in response to UVR with emphasis on the dynamics of skin cancer development. During model construction, validation and testing stages, clinical judgment from an expert dermatologist was sought. The model was used to analyze the ability of UVR to treat psoriasis as well as its contribution to skin cancer development. To deal with the apparent conflicting properties of such UVR-based therapy, a multi-objective evolutionary optimization in the form of Non-dominated Sorting Genetic Algorithm-II (NSGA-II) was employed in the analysis. Results from the study have demonstrated the usefulness of the bottom-up modeling approach through multiagent systems in the elucidation of the role of cellular mechanisms such as apoptosis in skin cancer development. Also,this study has proven the potential of coupling evolutionary optimization algorithms to agent-based models in order to suggest possible dosimetry of common therapeutic modalities such as phototherapy.